Laboratory measurement of factor replacement therapies in the treatment of congenital haemophilia: A United Kingdom Haemophilia Centre Doctors' Organisation guideline. Issue 1 (17th December 2019) - Gray, Elaine; Kitchen, Steve; Bowyer, Annette; Chowdary, Pratima; Jenkins, P. Vincent; Murphy, Paul; Platton, Sean; Riddell, Anne; Lester, Will
Abstract: Assay discrepancies can occur with laboratory monitoring of FVIII and FIX replacement therapy, particularly for the extended half‐life products. This guideline collates current published data and provides advice on appropriate choice of assays for laboratory measurement of replacement therapy for patients with Haemophilia A and B without inhibitors. It is recommended that each haemophilia centre should ensure that appropriate laboratory assays are available for FVIII and FIX products in local clinical use. Patient samples should be assayed against calibrators traceable to WHO Plasma International Standards. Assay discrepancies are common especially for the extended half‐life FVIII and FIX products, and assays of these products may need to be verified with the specific CFC being used.